1997
DOI: 10.1016/s0029-7844(97)00015-x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized comparison between misoprostol and dinoprostone for cervical ripening and labor induction in patients with unfavorable cervices

Abstract: Misoprostol is an effective agent for cervical ripening and labor induction, but it causes an increase in cesarean deliveries associated with uterine hyperstimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
1
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 9 publications
5
60
1
2
Order By: Relevance
“…Buser D et al in their study found greater CS rate in Misoprostol group (35.5% versus 21.5%). [6] Sanches-Ramos L et al, too found higher CS rate in Misoprostol group (22.2% versus 13%). [14] Regarding induction-delivery interval, Sahu L et al and Fernandez E et al found it to be shorter in Misoprostol group.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Buser D et al in their study found greater CS rate in Misoprostol group (35.5% versus 21.5%). [6] Sanches-Ramos L et al, too found higher CS rate in Misoprostol group (22.2% versus 13%). [14] Regarding induction-delivery interval, Sahu L et al and Fernandez E et al found it to be shorter in Misoprostol group.…”
Section: Discussionmentioning
confidence: 89%
“…[6] Ozan H et al also found that, 50 µg intra-vaginal misoprostol combined with oxytocin augmentation when necessary, was an effective and safe method of labour-induction. [10] The current study findings corroborate with their study finding.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…12 David Buser et al defined successful induction as the onset of good uterine contractions and a Bishops score >5. 13 By this parameter, too, Misoprostol was associated with more successful inductions. As with previously mentioned authors, Buser et al also reported more vaginal deliveries within 24 hours and a lesser need for oxytocin augmentation with Misoprostol use.…”
Section: Discussionmentioning
confidence: 91%
“…12 However, it is difficult to interpret previously published studies comparing misoprostol with dinoprostone for induction of labour since majority of them have included both complicated and uncomplicated pregnancies as well as a wide gestational age (GA) range (37-42 weeks). [13][14][15] Moreover, to reduce the risk of side effects, one can either decrease the dose of the drug or prolong the dosage interval. In addition, Alexander et al, have recently shown that in prolonged pregnancies it was not the induction per se that would increase the risk for caesarean section (CS), but was the patients-related risk factors such as undilated cervix.…”
Section: Introductionmentioning
confidence: 99%